2017
DOI: 10.1089/thy.2017.0158
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Iodine, Perchlorate, and Thiocyanate Concentrations in U.S. Lactating Women

Abstract: Lactating women in three U.S. geographic regions are iodine sufficient with an overall median UIC of 143 μg/L. Given ubiquitous exposure to perchlorate and thiocyanate, adequate iodine nutrition should be emphasized, along with consideration to decrease these exposures in lactating women to protect developing infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…We found similar median concentrations for maternal urinary thiocyanate and nitrate in this study and in our previously published work including non-lactating and non-pregnant women ( 15 ). Interestingly, the median maternal urinary thiocyanate concentrations (274 μg/L) in our study were relatively lower than the U.S. lactating women (514 μg/L) ( 27 ). We believe this discrepancy is not related to the number of active smokers in the study groups since only a few women actively smoked in both groups during lactation.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…We found similar median concentrations for maternal urinary thiocyanate and nitrate in this study and in our previously published work including non-lactating and non-pregnant women ( 15 ). Interestingly, the median maternal urinary thiocyanate concentrations (274 μg/L) in our study were relatively lower than the U.S. lactating women (514 μg/L) ( 27 ). We believe this discrepancy is not related to the number of active smokers in the study groups since only a few women actively smoked in both groups during lactation.…”
Section: Discussioncontrasting
confidence: 77%
“…We found that median urinary perchlorate concentration in Turkish lactating women (3.89 μg/L) was relatively higher than in the U.S. lactating women [3.0 μg/L ( 26 ), 3.1 μg/L ( 27 )]. This result is consistent with our previously published work, in which we evaluated urinary perchlorate concentrations in non-pregnant and non-lactating women and found that median urinary perchlorate concentration (6.4 μg/L) was more than twice as high as the median concentration found in U.S. women (2.9 μg/L) ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 83%
“…It is a common contaminant of foods and drinking water, and lactating women may be exposed through diet ( 289 ). Data in lactating women report a positive association between urinary concentrations of perchlorate and iodine ( 290 ), whereas the fractional excretion in breast milk is higher for perchlorate than for iodine ( 245 , 268 ). Although human data provide limited support for an inhibiting effect of perchlorate on BMIC, the studies are small and inconclusive ( 245 , 279 , 291-293 ).…”
Section: Iodine In Human Milkmentioning
confidence: 99%
“…Thiocyanate exposure is a strong risk factor for goiter ( 298 , 299 ), but likely secondary to iodine deficiency and at high thiocyanate intakes and inadequate protein nutrition ( 300 ). Urinary thiocyanate concentration positively correlates with UIC in lactating women ( 290 ), but a study conducted in cassava-eating mothers observed no correlation with thiocyanate concentration in maternal serum and breast milk ( 301 ). Thiocyanate excretion in human milk appears to be limited, indicated by low fractional excretion ( 268 , 300 ).…”
Section: Iodine In Human Milkmentioning
confidence: 99%
“…Chronic consumption of ClO 4 − in adults has been estimated as high as 0.07 to 0.34 µg/Kg of body weight per day in Europe [70], and 0.2 to 0.4 µg/Kg of body weight per day in the USA [74]. Despite ClO 4 − consumption being generally below the level of recommended reference dose in adults [75], it may become critical, especially in some categories, such as children, high sensitive patients, cigarette smokers, iodine deficient people, and pregnant and breast feeding women as well [76][77][78]. Indeed, the inhibition of I uptake and any potential downstream effects induced by ClO 4 − are strictly dependent on the exposure to other environmental NIS inhibitors, such as thiocyanates and nitrates, and iodine intake itself [79].…”
Section: Chronic Esposure To Perchlorate Compounds By Food and Drinkimentioning
confidence: 99%